Probiotics and their relationship with caries control: a topic review - Angarita-Díaz, María del Pilar (Revista Facultad de Odontología Universidad de Antioquia, 2016)
The development of studies related to the human oral microbiome, as well as the applied sciences and techniques to investigate it, have helped reconsidering our understanding of tooth decay as an endogenous infection caused by a conglomerate of microorganisms. In addition to identifying the great diversity of microorganisms involved in carious processes, similar studies in healthy oral cavity have also been conducted, as well as analysis of the interactions between microorganisms and the host. The results are paving the way to implementing biotechnology strategies to interrupt the onset and progression of the disease, and in this sense probiotics are a promising tool. Probiotics are beneficial microorganisms that once in contact with the oral cavity modify the microbial interaction favoring homeostasis. A literature review was conducted using various databases (PubMed, ScienceDirect, and Google Scholar), focusing on probiotics as a strategy for caries control, based on their function in the oral cavity; this includes some of the studies conducted so far as well as the description of features of the bacterial strains most commonly studied and the ones recently isolated. The article concludes by explaining the ideal features that bacterial strains should have to be efficient as probiotics in the oral cavity.